Application on Detecting Causality Relationships Between the Stock Markets of the Fragile Five Countries - Medetoğlu, Batuhan (İşletme Araştırmaları Dergisi, 2025)
Purpose – The aim of the study is to determine the relations between the stock markets of the Fragile Five Countries "BIITS" (Brazil, Indonesia, India, Türkiye and South Africa). The relationships obtained are intended to guide portfolio diversification and investment decisions. Design/methodology/approach – Within the scope of the study, Correlation Analysis and Granger Causality Analysis were applied to determine the relationships. In this context, data for the period 01.01.2010-31.12.2023 were obtained, and indicative stock market data of the countries were used. Direction and severity of relationships with Correlation Analysis; Causality relationships were also determined using the Granger Causality Test. As stated in the literature, determining the relationship between countries' stock markets is important for international portfolio investment. Findings – As a result of the analysis, a low or near medium level correlation was detected between the stock markets of the countries. Causality analysis revealed an intense relationship was found in general. It was concluded that Brazilian indicator exchange is also the Granger cause of the other four indicator exchanges. Discussion – It has also been concluded that relevant countries have a close causal relationship and can be used in terms of portfolio diversification. The results obtained were compatible with those reported in the literature. This study aims to guide investors, markets, and researchers